Dilemmas concerning the canon law (II) – bonum commune or communionis - GAŁKOWSKI, TOMASZ (Prawo Kanoniczne, 2016)
The author discusses the possibility of accepting common good as an internal element of the canon law. He presents the understanding of common good in philosophy and social sciences as well as in the social teaching of Church. He also points out at the statements of Paul VI and John Paul II, who spoke about common good in the community of Church. The author claims that there is a possibility of accepting common good as an element of the canon act. Thus, he refers to Thomas Acquinas and his understanding of common good as the common intentional cause of activity. The essence of common good is bonum communionis. Common good understood in this way is not excluded from the definition of the canon law, since as John Paul II maintained, obeying the canon norms contributes to the growth of the community of Church.